Semimetallicity and Negative Differential Resistance from Hybrid Halide Perovskite Nanowires. (7th January 2019) - Khan, Muhammad Ejaz; Lee, Juho; Byeon, Seongjae; Kim, Yong‐Hoon
Abstract: In the rapidly progressing field of organometal halide perovskites, the dimensional reduction can open up new opportunities for device applications. Herein, taking the recently synthesized trimethylsulfonium lead triiodide (CH3 )3 SPbI3 perovskite as a representative example, first‐principles calculations are carried out and the nanostructuring and device application of halide perovskite nanowires are studied. It is found that the 1D (CH3 )3 SPbI3 structure is structurally stable, and the electronic structures of higher‐dimensional forms are robustly determined at the 1D level. Remarkably, due to the face‐sharing [PbI6 ] octahedral atomic structure, the organic ligand‐removed 1D PbI3 frameworks are also found to be stable. Moreover, the PbI3 columns avoid the Peierls distortion and assume a semimetallic character, contradicting the conventional assumption of semiconducting metal‐halogen inorganic frameworks. Adopting the bundled nanowire junctions consisting of (CH3 )3 SPbI3 channels with sub‐5 nm dimensions sandwiched between PbI3 electrodes, high current densities and large room‐temperature negative differential resistance (NDR) are finally obtained. It will be emphasized that the NDR originates from the combination of the near‐Ohmic character of PbI3 ‐(CH3 )3 SPbI3 contacts and a novel NDR mechanism that involves the quantum‐mechanical hybridization between channel and electrode states. This work demonstrates the great potential of low‐dimensional hybrid perovskites toward advanced electronic devices beyond actively pursued photonic applications. Abstract : The unique semimetallicity and negative differential resistance (NDR) characteristics can be derived from organic–inorganic halide perovskite nanowires . The PbI3 nanowire, the inorganic framework of trimethylsulfonium lead triiodide (TMSPbI3 ), is found to assume a semimetallic character by avoiding the Peierls distortion. Excellent NDR characteristics are predicted to arise from the TMSPbI3 ‐PbI3 nanowire junctions with near‐Ohmic contacts through a novel quantum‐hybridization NDR mechanism.